2011
DOI: 10.1093/chrsci/49.10.825
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Tetrabutylammonium Ion-Pairing Reagent Distribution in a Gradient Elution of Reversed Phase Ion-Pair Chromatography

Abstract: The regeneration of ion-pairing reagent distribution on liquid chromatography columns after gradient elution has been well recognized as the cause for long column equilibration time, a major drawback associated with gradient elution reverse phase ion-pair chromatography. To date, the majority of studies have focused on optimizing the separation conditions to shorten the equilibration time. There is limited understanding of the ion-pairing reagent distribution process between the mobile phase and stationary ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Reproducibility in retention times among different days was evaluated since the ion pairing approach could be problematic especially due to changes in the concentration of the ion-pairing reagent on the surface of the column material [24,25]. We found that nucleobases and nucleosides presented, on average, less than 0.15 minutes of variability in retention time compared to their phosphorylated counterparts, which varied from 0.5 to 0.9 minutes over the period of 24 hours when only 1.25 mM DBAA was present in eluent B.…”
Section: Resultsmentioning
confidence: 99%
“…Reproducibility in retention times among different days was evaluated since the ion pairing approach could be problematic especially due to changes in the concentration of the ion-pairing reagent on the surface of the column material [24,25]. We found that nucleobases and nucleosides presented, on average, less than 0.15 minutes of variability in retention time compared to their phosphorylated counterparts, which varied from 0.5 to 0.9 minutes over the period of 24 hours when only 1.25 mM DBAA was present in eluent B.…”
Section: Resultsmentioning
confidence: 99%
“…For method robustness, we utilized mixed mode chromatography coupled with multiple‐reaction‐monitoring (MRM) instead of ion‐pairing chromatography (e.g. ion pairing reagent can have deteriorating effects on mass spectrometer) . The applicability of the developed method was demonstrated on a study of feed medium stability over a typical life span in fed‐batch cell culture processing.…”
Section: Introductionmentioning
confidence: 99%
“…ion pairing reagent can have deteriorating effects on mass spectrometer). 34 The applicability of the developed method was demonstrated on a study of feed medium stability over a typical life span in fed-batch cell culture processing. In addition, flexibility of our method was demonstrated by inclusion of additional compounds of interest to identify CDM-related reaction products described in the literature including methionine sulfone, cysteic acid, lumichrome, N-formylkynurenine, 3-hydroxy-DL-kynurenine, L-cysteinsulfinic acid, 3-aminopropionamide, hydroxocobalamin, 5-hydrody-L-tryptophan, DL-o-tyrosine, DL-methionine sulfoxide and L-citrulline.…”
Section: Introductionmentioning
confidence: 99%
“…inuences the chromatographic performance of the system can be attributed to their ranking in the Hofmeister series. 37 The rationalization of the different equilibria that can be in such system is not trivial; indeed, while the adsorption of IP agent on the hydrophobic stationary phase has been and profoundly evaluated, 38,39 and a rationale of the behavior of inorganic additive in RPLC has been assessed, [40][41][42][43][44] the presence of both additives has not yet been taken into consideration, as well as a comprehensive theoretical model. However, it is not a technique that can be interfaced with mass spectrometry due to the low volatility of IP agents.…”
Section: Resultsmentioning
confidence: 99%